Development of Comic Learning Media in Class XI SMK Negeri 2 Botomuzoi - Apriyanus Faahakho Dodo Harefa; Imansudi Zega; Riana (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Teachers should demonstrate greater creativity in creating and enhancing instructional materials. But because SMK Negeri 2 Botomuzoi lacks the infrastructure and equipment expressly meant to promote Indonesian language instruction, teachers there continue to employ a restricted and repetitious amount of media. In order to ensure that the learning materials are reliable, useful, and efficient, this project will create comic-based learning materials for assessing the language and content of theater in the eleventh grade at SMK Negeri 2 Botomuzoi. This study uses the ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation, as part of its research and development (R&D) methodology. Three specialists in material, language, and design evaluated the comic-based learning materials, which were then put to the test through product testing with TKJ students in the 11th grade at SMK Negeri 2 Botomuzoi. Thanks to validation scores of 97.5% from material experts, 100% from language experts, and 95% from design experts, the results show that the comic learning medium is both viable and legitimate. The learning media was rated as being very practical when it came to practicality; it received scores of 86.7% in solo testing, 94.2% in small group tests, and 93.9% in field tests. With a classical completion percentage of 96.3%, it was also proved that the learning media's effectiveness was very high. In conclusion, the ADDIE model was used to generate comic-based learning materials that analyze the language and content of drama in the 11th grade at SMK Negeri 2 Botomuzoi. These materials satisfy the required standards and may be used in the classroom.